Utilization of CT Pulmonary Angiography in Suspected Pulmonary Embolism in a Major Urban Emergency Department. (29th August 2013) - Shujaat, Adil; Shapiro, Janet M.; Eden, Edward
Abstract : Objectives . We conducted a study to answer 3 questions: (1) is CT pulmonary angiography (CTPA) overutilized in suspected pulmonary embolism (PE)? (2) What alternative diagnoses are provided by CTPA? (3) Can CTPA be used to evaluate right ventricular dilatation (RVD)? Methods . We retrospectively reviewed the clinical information of 231 consecutive emergency department patients who underwent CTPA for suspected PE over a one-year period. Results . The mean age of our patients was 53 years, and 58.4% were women. The prevalence of PE was 20.7%. Among the 136 patients with low clinical probability of PE, a d-dimer test was done in 54.4%, and it was normal in 24.3%; none of these patients had PE. The most common alternative findings on CTPA were emphysema (7.6%), pneumonia (7%), atelectasis (5.5%), bronchiectasis (3.8%), and congestive heart failure (3.3%). The sensitivity and negative predictive value of CTPA for (RVD) was 92% and 80%, respectively. Conclusions . PE could have been excluded without CTPA in ~1 out of 4 patients with low clinical probability of PE, if a formal assessment of probability and d-dimer test had been done. In patients without PE, CTPA did not provide an alternative diagnosis in 65%. In patients with PE, CTPA showed the potential to evaluate RVD.